2015
DOI: 10.3928/01477447-20150402-59
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Patient-Specific Instrumentation Compared With Conventional Instrumentation in Total Knee Arthroplasty

Abstract: Patient-specific instrumentation (PSI) has recently been introduced to improve the alignment following total knee arthroplasty (TKA). However, controversy remains between PSI and conventional instrumentation. The aim of this study is to compare the accuracy of PSI with conventional instruments for total knee arthroplasty (TKA). A systematic literature search was performed in databases including PubMed, the Cochrane Library, EMBASE, and Web of Science. All of the available randomized, controlled trials (RCTs) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 40 publications
0
31
1
Order By: Relevance
“…Regarding alignment data, Mannan et al demonstrated comparable restitution of a neutral postoperative mechanical axis, 23 as well as favorable femoral axial alignment in patient-specific instrumented knee arthroplasty. 4 Jiang et al, 5 Shen et al, 6 Cavaignac et al, 7 Thienpont et al, 8 Fu et al, 9 and Russell et al 11 reported similar findings for postoperative mechanical axis. Increased accuracy of reproduction of a target femoral coronal alignment has been reported in several meta-analyses with PSI (Cavaignac et al, 7 Thienpont et al, 8 A picture, therefore, emerges of comparable alignment outcomes in PSI versus conventional instrumentation with a trend toward favorable outcomes in several parameters in PSI (Mannan and Smith, 4 Cavaignac et al, 7 Thienpont et al, 8 and Voleti et al 10 ).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Regarding alignment data, Mannan et al demonstrated comparable restitution of a neutral postoperative mechanical axis, 23 as well as favorable femoral axial alignment in patient-specific instrumented knee arthroplasty. 4 Jiang et al, 5 Shen et al, 6 Cavaignac et al, 7 Thienpont et al, 8 Fu et al, 9 and Russell et al 11 reported similar findings for postoperative mechanical axis. Increased accuracy of reproduction of a target femoral coronal alignment has been reported in several meta-analyses with PSI (Cavaignac et al, 7 Thienpont et al, 8 A picture, therefore, emerges of comparable alignment outcomes in PSI versus conventional instrumentation with a trend toward favorable outcomes in several parameters in PSI (Mannan and Smith, 4 Cavaignac et al, 7 Thienpont et al, 8 and Voleti et al 10 ).…”
Section: Discussionmentioning
confidence: 75%
“…The results of this meta-analysis demonstrate equivalent functional outcomes between PSI and conventional instrumentation with follow-up of 3 to 24 months. Several published meta-analyses have described component alignment, [4][5][6][7][8][9][10][11] but this is the first in our knowledge to comprehensively synthesize functional data. Regarding alignment data, Mannan et al demonstrated comparable restitution of a neutral postoperative mechanical axis, 23 as well as favorable femoral axial alignment in patient-specific instrumented knee arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Initial proponents of this technology also suggested that it could help in minimizing blood loss, and 34 improve clinical outcome [10,21,30]. 35 Preliminary studies confirmed that PSI is effective in reducing surgical time [9,10,13,14,16,20,36 21] and may help to achieve better prosthetic component position and sizes in TKA [10,21,30], but 37 recent reviews suggested care when interpreting these initial results [18,29]. 38 Computer software can indeed facilitate pre-operative planning and help predicting intra-operative 39 resections and component sizes.…”
mentioning
confidence: 99%
“…Therefore, a new technology that could reduce the proportion of incorrectly aligned implants appears appealing. However, there is controversy in the available published literature on the ability of PSI to affect the implant positioning, with some studies showing increased accuracy of femoral rotation with the use of PSI [8][9][10][11] and others revealing no differences from conventional alignment techniques [12][13][14][15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%